Green Manufacturing Practices and Sustainable Industrial Performance: A Mixed-Methods Study of Environmental Innovation in Indonesian Manufacturers - Sokha Sopheat (Techne: Journal of Engineering, Technology and Industrial Applications, 2026)
This study examined how green manufacturing practices influence sustainable industrial performance through environmental innovation implementation in Indonesian manufacturing firms. A sequential explanatory mixed-methods design was applied. Quantitative data were collected from 128 managers and supervisors in 24 manufacturing firms using a structured questionnaire and analyzed with partial least squares structural equation modeling. Qualitative evidence came from 16 semi-structured interviews with production, quality, maintenance, and environmental managers from high- and moderate-adopting firms. Green manufacturing practices were strongly associated with environmental innovation implementation (beta = 0.63, p < .001) and directly with sustainable industrial performance (beta = 0.29, p < .001). Environmental innovation implementation also predicted sustainable industrial performance (beta = 0.47, p < .001) and partially mediated the relationship between green manufacturing and performance. The model explained 40% of the variance in environmental innovation implementation and 69% of the variance in sustainable industrial performance. Interview data showed that energy monitoring, waste segregation, process digitization, and supplier coordination were the main levers of improvement, while capital intensity and skills gaps remained the main constraints. Green manufacturing contributed to higher sustainable industrial performance when firms translated environmental intentions into process-level innovations and measurement routines. The findings support a capability-based view of sustainability implementation and indicate that managerial attention should shift from symbolic environmental claims to operational redesign, data visibility, and cross-functional discipline.